Упростите выражение 2/х2-9+ 1/х-3 - 2/х+3

Упростите выражение 2/х2-9+ 1/х-3 - 2/х+3
Гость
Ответ(ы) на вопрос:
Гость
[2+х+3-2(x-3)]/x^2-9 (5+x-2x+6)/x^2-9 (11-x)/x^2-9 как-то не оч вышло... точно так написано?
Гость
[latex] \frac{2}{x^2-9} + \frac{1}{x-3} - \frac{2}{x+3} = \frac{2}{(x-3)(x+3)} + \frac{1}{x-3} - \frac{2}{x+3} = \frac{2+1(x+3)-2(x-3)}{(x-3)(x+3)} = [/latex][latex] \frac{2+x+3-2x+6}{(x-3)(x+3)} = \frac{-x+11}{(x-3)(x+3)} = \frac{-x+11}{x^2-9} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы